De-escalating and escalating treatments for early-stage breast cancer: the St. Gallen International Expert Consensus Conference on the Primary Therapy of Early Breast Cancer 2017 - GÜLLÜOĞLU, MAHMUT BAHADIR (OXFORD UNIV PRESS, 2017)
The 15th St. Gallen International Breast Cancer Conference 2017 in Vienna, Austria reviewed substantial new evidence on loco-regional and systemic therapies for early breast cancer. Treatments were assessed in light of their intensity, duration and side-effects, seeking where appropriate to escalate or de-escalate therapies based on likely benefits as predicted by tumor stage and tumor biology. The Panel favored several interventions that may reduce surgical morbidity, including acceptance of 2 mm margins for DCIS, the resection of residual cancer (but not baseline extent of cancer) in women undergoing neoadjuvant therapy, acceptance of sentinel node biopsy following neoadjuvant treatment of many patients, and the preference for neoadjuvant therapy in HER2 positive and triple-negative, stage II and III breast cancer. The Panel favored escalating radiation therapy with regional nodal irradiation in high-risk patients, while encouraging omission of boost in low-risk patients. The Panel endorsed gene expression signatures that permit avoidance of chemotherapy in many patients with ER positive breast cancer. For women with higher risk tumors, the Panel escalated recommendations for adjuvant endocrine treatment to include ovarian suppression in premenopausal women, and extended therapy for postmenopausal women. However, low-risk patients can avoid these treatments. Finally, the Panel recommended bisphosphonate use in postmenopausal women to prevent breast cancer recurrence. The Panel recognized that recommendations are not intended for all patients, but rather to address the clinical needs of the majority of common presentations. Individualization of adjuvant therapy means adjusting to the tumor characteristics, patient comorbidities and preferences, and managing constraints of treatment cost and access that may affect care in both the developed and developing world.
Keywords: St Gallen Consensus; early breast cancer; radiation therapy; surgery; systemic adjuvant therapies; CARCINOMA IN-SITU; 21-GENE RECURRENCE SCORE; LYMPH-NODE BIOPSY; NEOADJUVANT CHEMOTHERAPY; DOUBLE-BLIND; POSTMENOPAUSAL WOMEN; AXILLARY DISSECTION; CONSERVING SURGERY; DISTANT RECURRENCE; ENDOCRINE THERAPY